A Comparative Study of Mathematics Education in the United States and Nepal - Belbase, Shashidhar (Mathematics Education Forum Chitwan, 2019)
The purpose of this paper is to compare four domains of mathematics education-curricular materials, pedagogical process, teacher education, and assessment of students’ learning in the United States of America (USA) and Nepal. I applied categorical thinking for document analysis from the literature to find some key concepts related to the four categories of comparison. The Common Core State Standards for Mathematics (CCSSM) is a major curriculum standard implemented in many states in the USA, whereas, the National Curriculum Framework (NCF) is the major policy document that guides school mathematics curricula in Nepal. Mostly, classroom practices are student-centred with problem-solving, reasoning and critical thinking in the USA, but it is mostly drill-and-practice in Nepal. Preservice mathematics teacher education in the USA and Nepal are conducted by universities, but there is a vast difference in the courses offered in these countries. Assessment of students’ learning in mathematics is continuously done in classroom activities and exams including some standardized exams in selected grades in the USA, whereas, assessment in Nepal is done with periodic and final exams including standardized district and national tests in selected grades. I discussed some implications of the study.